Total IgE Levels in Atopic Dermatitis Patients - İlhan, Fulya; Akbulut, Handan; Coşkun, Başak Kandi (Fırat University, 2005)
Objectives: Atopic dermatitis is the first step of atopic process resulting in asthma and allergic rhinitis. Clinical phenotype of atopic dermatitis is a result of interactions among broken skin barrier function, environmental effects, genetical tendency and immunological response. Th2 lymphocytes, their cytokines and especially IgE production and eosinophils have important roles on the pathogenesis of atopic dermatitis. In this study it was aimed to measure total IgE levels in 23 patients with atopic dermatitis and to compare with these results to healthy controls. Materials and Methods: Twenty three patients with atopic dermatitis whose age ranging from 8 to 35 (mean ± SE 21.77±2.88) and 23 healthy volunteer whose age ranging from 18 to 32 (mean ± SE 25±3.22) were obtained in Dermatology Department of Firat University Research Center. Blood samples were collected and separated serums stored in –80 ºC until study. Total IgE levels were measured with ELISA. Statistical analysis was made by Student's T test using SPSS 11.0 and p

Amaç: Atopik dermatit sıklıkla astma ve alerjik rinit ile sonuçlanan atopik gidişin ilk basamağıdır. Atopik dermatitle karakterize klinik fenotip; bozulmuş cilt bariyer fonksiyonu, çevresel etkenler, hassas genler ve immünolojik cevaplar arasındaki etkileşimin bir sonucudur. Atopik dermatitin patogenezinde Th2 lenfositler ve bunların sitokinleri ile immünglobulin IgE (IgE ) ve eozinofiller büyük rol oynarlar. Bu çalışmada atopik dermatit tanısı alan 23 hastada total IgE değerleri araştırıldı ve sağlıklı kontrol ile karşılaştırıldı. Gereç ve Yöntem: Fırat Üniversitesi Tıp Fakültesi Dermatoloji Anabilim Dalı'nda atopik dermatit tanısı konan ve yaşları 8-35 (ortalama 21.77±2.88) arasında olan 23 olgu ile, 18-32 yaşları arasında olan 23 sağlıklı gönüllüden 2ml venöz kan alındı. Santrifüj edilen kanların serumları ayrılarak çalışma gününe kadar -80 ºC de derin dondurucuda bekletildi. Hasta ve kontrol serumlarından total IgE ölçümleri ELİSA yöntemiyle yapıldı. Verilerin karşılaştırılması SPSS 11.0 programı kullanılarak Student's T testi ile yapıldı ve p
Atopik Dermatitli Hastalarda Total IgE Değerleri